1998
DOI: 10.1017/s1350482798001005
|View full text |Cite
|
Sign up to set email alerts
|

A fuzzy expert system to assist in the prediction of hazardous wind conditions within the Mediterranean basin

Abstract: An expert system (MEDEX) for predicting the gale-force onset, continuation, and cessation of seven major wind types within the Mediterranean basin has been designed, developed, and tested. The six wind types consist of the bora (flowing through both the Adriatic and Aegean Seas), etesian, levante, mistral, sirocco and westerly (poniente and vendaval

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…This is a standard approach in designing fuzzy expert systems: acquiring knowledge from experts and encoding it in fuzzy rules (Kuciauskas et al 1998;Meyer et al 2002). The motivation for combining fuzzy operations with the analog method is not to objectively measure similarity, nor is it to somehow * For example, for ceiling height, a value of 3 ⁄4 implies that if the lower ceiling is 600 ft and the higher ceiling is 800 ft, then they will be described with words such as "very similar" and with ϭ 0.9.…”
Section: Fuzzy Similarity-measuring Algorithmmentioning
confidence: 99%
“…This is a standard approach in designing fuzzy expert systems: acquiring knowledge from experts and encoding it in fuzzy rules (Kuciauskas et al 1998;Meyer et al 2002). The motivation for combining fuzzy operations with the analog method is not to objectively measure similarity, nor is it to somehow * For example, for ceiling height, a value of 3 ⁄4 implies that if the lower ceiling is 600 ft and the higher ceiling is 800 ft, then they will be described with words such as "very similar" and with ϭ 0.9.…”
Section: Fuzzy Similarity-measuring Algorithmmentioning
confidence: 99%
“…Additionally, they can contribute to the rapid spread of forest fires. The importance of this wind regime is highlighted by the fact that it is a weather type incorporated by the US Navy in their fuzzy expert system to assist in the prediction of hazardous wind conditions in the Mediterranean basin (Kuciauskas et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Because the borders of classification of weather conditions in thermal mapping are noncrisp, the problem should be dealt with by fuzzy set theory (Zadeh 1965;Zimmermann 1991). Research has shown that fuzzy set theory can be a valuable tool for meteorologists (e.g., Cao and Chen 1983;Boreux 1994;Kuciauskas et al 1998;Maner and Joyce 1997;McBratney and Moore 1985;Murtha 1995).…”
Section: Fuzzy Categorizationmentioning
confidence: 99%